PROFIL KEMANDIRIAN BELAJAR SISWA SMPN 26 KOTA TANGERANG - Dinda Agustini; Raudah Zaimah Dalimunthe; Alfiandy Warih Handoyo (STKIP Subang, 2026)
This study aims to describe the profile of students’ learning independence at SMPN 26 Kota Tangerang, which includes four main aspects: decision-making ability, responsibility for academic tasks, learning initiative, and self-discipline. The background of this research stems from the observation that several students still exhibit dependency in the learning process, resulting in suboptimal development of independent learning skills. This study employed a quantitative approach with a descriptive method. The research instrument consisted of a learning independence questionnaire administered to the selected student sample. The findings reveal that the overall level of learning independence among students at SMPN 26 Kota Tangerang falls within the moderate to high category. In the aspect of decision-making ability, students generally demonstrated the capacity to determine their learning choices independently, although some still required guidance. Responsibility for completing academic tasks was categorized as moderate, with many students showing inconsistency in submitting assignments on time. Students’ learning initiative was relatively good but not evenly distributed among all respondents. The self-discipline aspect indicated that most students were able to manage their learning behavior; however, some continued to show tendencies to procrastinate. Overall, the study concludes that students’ learning independence has developed well but still requires targeted interventions and counseling programs to strengthen certain aspects. The results of this study are expected to provide valuable input for guidance and counseling teachers, subject teachers, the school, and future researchers in efforts to optimize students’ independent learning skills.